The amino-terminal hydrophilic region of the vacuolar transporter Avt3p is dispensable for the vacuolar amino acid compartmentalization of Schizosaccharomyces pombe. Issue 12 (1st December 2016) - Kawano-Kawada, Miyuki; Chardwiriyapreecha, Soracom; Manabe, Kunio; Sekito, Takayuki; Akiyama, Koichi; Takegawa, Kaoru; Kakinuma, Yoshimi
Abstract: Avt3p, a vacuolar amino acid exporter (656 amino acid residues) that is important for vacuolar amino acid compartmentalization as well as spore formation in Schizosaccharomyces pombe, has an extremely long hydrophilic region (approximately 290 amino acid residues) at its N-terminus. Because known functional domains have not been found in this region, its functional role was examined with a deletion mutant avt3 (∆1–270) expressed in S. pombe avt3 ∆ cells. The deletion of this region did not affect its intracellular localization or vacuolar contents of basic amino acids as well as neutral ones. The defect of avt3 Δ cells in spore formation was rescued by the expression of avt3 + but was not completely rescued by the expression of avt3 (∆1–270) . The N-terminal region is thus dispensable for the function of Avt3p as an amino acid exporter, but it is likely to be involved in the role of Avt3p under nutritional starvation conditions. Graphical abstract: : The N-terminal long hydrophilic region of Schizosaccharomyces pombe Avt3p is suggested to be dispensable for the function as an amino acid exporter.